REGULATORY AND LEGAL BASIS OF PROCESSES RELATED TO INTANGIBLE ASSETS AND THEIR MOVEMENT - Ishankulov Izzatilla Nurullayevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
In this thesis, the regulatory and legal bases of the processes related to tangible assets and their movement are studied, and proposals are developed.